The variation of protein, sugars, and organic acids in oat hulls after bioprocessing with enzymes - Amirthalingam, Sambavi (My University, 2024)
Oat (Avena sativa) production is increasing due to its health benefits and the growing shift towards plant based diets. This resulted in a significant level of oat hulls (OH) generation, eventually considered waste. This study aimed to use a green method to extract nutrients from OH for innovative food applications. Enzymatic hydrolysis was used to change the chemical composition of OH by breaking down its recalcitrant structure and increasing nutrient extractability. The goal was to enhance food resource efficiency and sustainability. Samples were treated with ultrasound assisted enzymatic hydrolysis using commercial food grade carbohydrases, feruloyl esterase, proteases, and their combinations. Supernatants were analyzed for protein content using the Kjeldahl method, and free sugars and organic acids content using GC-FID. Oligosaccharides were examined using UHPLC-ELSD. The data were statistically analyzed with SPSS and Unscrambler. Results showed increased protein content, free sugars, and organic acids in enzyme treated samples, with combination treatments being the most effective. The combination treatment resulted in the highest protein content of 69.0 g/100 g OH DM, total sugar content of 65.8 g/100 g OH DM, and organic acids content of 1.7 g/100 g OH DM. Protease treated samples indicated the tentative presence of oligosaccharides. These findings suggest the potential of utilizing OH in new food products, promoting sustainability and efficient use of food resources.
Keywords: Avena sativa, food grade enzymes, free sugars, oat hulls, oligosaccharides, organic acids, proteins, ultrasonication